P-Alkynyl functionalized benzazaphospholes as transmetalating agents. Issue 2 (6th January 2021) - Zhou, Daniel Y.; Miura-Akagi, Preston M.; McCarty, Sierra M.; Guiles, Celeste H.; O'Donnell, Timothy J.; Yoshida, Wesley Y.; Krause, Colleen E.; Rheingold, Arnold L.; Hughes, Russell P.; Cain, Matthew F.
Abstract : Exposure of 10π-electron benzazaphosphole 1 to HCl, followed by nucleophilic substitution with the Grignard reagent BrMgCCPh afforded alkynyl functionalized 3 featuring an exocyclic –CC–Ph group with an elongated P–C bond (1.7932(19) Å). Abstract : Exposure of 10π-electron benzazaphosphole 1 to HCl, followed by nucleophilic substitution with the Grignard reagent BrMgCCPh afforded alkynyl functionalized 3 featuring an exocyclic –CC–Ph group with an elongated P–C bond (1.7932(19) Å). Stoichiometric experiments revealed that treatment of trans -Pd(PEt3 )2 (Ar)(i ) (Ar = p -Me (C ) or p -F (D )) with 3 generated trans -Pd(PEt3 )2 (Ar)(CCPh) (Ar = p -Me (E ) or p -F (F )), 5, which is the result of ligand exchange between P–I byproduct 4 and C/D, and the reductively eliminated product (Ar–CC–Ph). Cyclic voltammetry studies showed and independent investigations confirmed 4 is also susceptible to redox processes including bimetallic oxidative addition to Pd(0) to give Pd(i ) dimer 6-Pd2 -(P( t -Bu)3 )2 and reduction to diphosphine 7 . During catalysis, we hypothesized that this unwanted reactivity could be circumvented by employing a source of fluoride as an additive. This was demonstrated by conducting a Sonogashira-type reaction between 1-iodotoluene and 3 in the presence of 10 mol% Na2 PdCl4, 20 mol% P( t -Bu)Cy2, and 5 equiv. of tetramethylammonium fluoride (TMAF), resulting in turnover and the isolation of Ph–CC–( o -Tol) as the major product.